A utilização da gestão por competências: estudo de caso em duas empresas. - Silva, Marco Antonio Costa da (2005)
This dissertation analyzes concrete cases of introduction of the competence management, to know how the changes in the work organization were associated with it. The literature about competences has advanced in the last years, not only in volume of publications, but also in the dimensions of analysis of the subject. The competence management was introduced in these organizations as a management model that would give sustentation to a more general process of change that the companies were passing by, giving the managers the support to validate their decisions. It was traced a picture about organizational changes related to work and human resources practices and its relation to the introduction of competence management. Later, an analysis was carried through concrete cases removed from the literature about introduction of the competence management. Finally, a research was conducted in two companies of different sectors that introduced the competence management. For this, interviews were realized with human resources and production managers and with operational workers. The results of the research showed that the companies have adopted the competence management as part of a wider process of reorganization. It was verified that the companies prioritized the development of individual abilities e the more important initiatives related to the competence management are related to the practices of training and performance development and evaluation.